Social Media Management of the Instagram Account @sdmuhammadiyahparakan Using the Circular Model of Some Approach in Building Relationships with Parents for the 2024- 2025 Period - Fadhlan Hafiyyan Muhammad; Adhianty Nurjanah (Jogjakarta Communication Conference (JCC), 2026)
Influencer In the digital age, social media has become a potential tool for schools to convey information and establish communication with parents and the community. Unfortunately, many elementary schools are still unaware of the importance of maximizing the use and management of social media to build relationships with parents. Meanwhile, SD Muhammadiyah Parakan utilizes Instagram as a digital communication medium to convey information and establish relationships with parents. This study aims to describe and analyze the management of SD Muhammadiyah Parakan's Instagram account in building relationships with parents’ period 2024- 2025 using The Circular Model of Some approach. The research method used is qualitative descriptive with data collection through documentation and in-depth interviews with the Head of the Media Division of the elementary school, the Instagram Admin of SD Muhamadiyah Parakan, and the parents of the elementary school students. The results of the study prove that SD Muhammadiyah Parakan has implemented digital communication management based on The Circular Model of Some through its Instagram account @sdmuhammadiyahparakan. In terms of share, Instagram is the main medium for sharing school information about teaching and learning activities and student achievements, thereby generating active interaction with parents. In terms of optimize, content is maximized using photography, videography, and structured, characterful narrative texts, accompanied by the use of Instagram features. In terms of manage, team coordination and cooperation are fairly organized, but are still constrained by the team's main responsibility as teachers and the lack of a dedicated platform for social media management. In terms of engage, the school has involved students, parents, and news media through comments on posts, direct messages, and the content production process. This strategy has the potential to actively and massively build relationships with parents, although the school is still not optimal in managing the workflow and performance of the creative media team.